O princípio da função social da atividade empresarial verdade, paradoxo, complexidade e formas jurídicas - Delgado, Herleide Herculano (2016)
This work is the result of research done on the principle of the social function of business activity, while economic private property, provisions of Article 170 of the Federal Constitution. It aims to unveil the standardized paradox of transfer of a government bond for an activity that is in its nature, unique and exclusively, getting the profit, as well as specific objectives: to expose the issue under the logic of systems theory and constructivism, making an interlacing, in a dialectic between the liberal economic thought Enlightenment and the thought of autopoietic systemic logic, as well as to increase the position of observation of the social system and its subsystems, to expand the cognitive capacity of observers with in order to foster the creation of legal possibilities and new theories to the complexities generated by the contingencies and the speed of changing society. The study proposed here, was due to the finding of ineffectiveness, in practice, the above constitutional economic principle and by observing the lack of studies of this issue from a legal critical bias, constructivist theory, systemic and philosophical theory, with the intention to expand discussions that around and contribute to the academic and social community. Throughout the research to date, it was possible to see a vast field for exploration of academic debates and discussions within the language, communication of the various understandings and new knowledge to work with the social dynamics.